Religious activities of students and understanding of Buddhist teachings at SMB Bodhisattva - Heni Angga Sari; Sutiyono Sutiyono; Ayu Andriyaningsih (International Journal of Science and Applied Science: Conference Series, 2025)
Religious activities at Bodhisattva Buddhist Sunday School (SMB), such as devotional worship, meditation, paritta recitation, and religious character building, are an integral part of religious education. However, there is still a gap between the level of student participation in these activities and their understanding of Buddhist teachings. This study aims to analyze the relationship between students' religious activities and their level of understanding of Buddhist teachings at SMB Bodhisattva. The method used is a quantitative approach with a correlational design through a survey technique. The sample was taken saturately from 100 active students at SMB Bodhisattva. The research instrument was a closed questionnaire using a Likert scale. Data analysis was performed using Pearson's correlation test through SPSS version 26. The results showed a positive and significant relationship between involvement in religious activities and understanding of Buddhist teachings. The indicators of worship and religious character habits contributed the most to this understanding. These findings confirm that consistent religious participation can shape students' understanding of the core values of Dhamma, such as the Four Noble Truths, the Law of Karma, and the Noble Eightfold Path. This study highlights the importance of integrating spiritual experiences into the non-formal Buddhist education process. The practical implications include the need for collaboration between SMB administrators, teachers, parents, and the temple community to create a conducive learning ecosystem for shaping a spiritually and ethically superior Buddhist generation.